PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS V SDN 22 DURI BARAT - Rini Siska; Hendri Marhadi; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This research is motivated by the lack of civics student learning outcomes, it can be seen from the results of learning civics students with a grade average grade 69.50. This study aims to improve student learning outcomes Civics class V SD Negeri 22 Duri Barat Application of Cooperative Learning Model with the kind of Student Team Achievement Division (STAD). Design research is action research (PTK) with two cycles .. Based on the analysis of research data after applying cooperative learning model Student Team Achievement Division (STAD) the percentage of the first meeting of the first cycle of teacher activity increased 62.5% 70.83% at the second meeting. The percentage of activity the teachers in the second cycle the first meeting of 79.16% and increased in the second meeting of the second cycle into 91.66%. The percentage of student activity first meeting of the first cycle of 54% and a second meeting increased to 58.33%, also increased from 83% at the first meeting of the second cycle, increased to 87.5% in the second meeting of the second cycle. learning outcomes in basic score with the average value of 69.50 and the first cycle of students increased by an average value of 75.75 with an increasing percentage of classroom learning results of 8.25% and the percentage of students who complete 70%, and in cycle II increased to an average of 82.25 with the percentage improvement class learning outcomes 15.50% and the percentage of students who complete 85%. These results show that the implementation of cooperative learning model Student Team Achievement Division (STAD), can improve student learning outcomes Civics class V SD Negeri 22 Duri Barat. Keywords: Student Teams Achievement Division, learning outcomes Civics